Self-parody in Igor Severyanin’s poetry (poems "July Noon" and "A carriage") - Галкина, Яна Викторовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
Poetic particular of ego-futurist Igor Severyanin’s poems “The July Noon" (1910) and " The carriage" (1918) are considered in the article. The poem “The carriage" is a parody on the text "The July afternoon." Igor Severyanin parodies the important for his poetry theme of hedonism and idleness. The analysis helps to understand the evolution of the author’s style, and the perception of changes in the cultural environment. Severyanin’s "double" irony is the reaction to loosening of postsimbolist poetics after the revolution and to the crisis of his own poetic practice.